The Prognosis of Endometriosis Correlates With Elevated Expression of LncRNA-ANRIL - Gao Jiayin; Quratul Ain; Sun Haizhu; Xiaohong Qiu; Zhang Song (Obstetrics and Gynecology International)
Conclusions: There was a positive correlation between the expression of ANRIL and the occurrence of endometriosis. Additionally, there was a close association between the expression of ANRIL and the etiology and development of endometriosis. This offers a potential basis for the early detection and treatment of endometriosis.